On the electronic structure of niII complexes that feature chelating bisguanidine ligands - Roquette, Pascal; Maronna, Astrid Christine; Peters, Anastasia; Kaifer, Elisabeth; Himmel, Hans-Jörg; Hauf, Christoph; Herz, Verena; Scheidt, Ernst-Wilhelm; Scherer, Wolfgang (Chemistry - a European journal, 2010)
In this work we report on the syntheses and properties of several new Ni complexes featuring the chelating bisguanidines bis(tetramethylguanidino)benzene (btmgb), bis(tetramethylguanidino)naphthalene (btmgn), and bis(tetramethylguanidino)biphenyl (btmgbp) as ligands. All complexes were structurally characterized by single-crystal X-ray diffraction and quantum chemical calculations. A detailed inspection of the magnetic susceptibility of [(btmgb)NiX2] and [(btmgbp)NiX2] (X=Cl, Br) revealed a linear temperature dependence of χ−1(T) above 50 K, which was in agreement with a Curie-Weiss-type behavior and a triplet ground state. Below approximately 25 K, however, magnetic susceptibility studies of the paramagnetic d8 Ni complexes revealed the presence of a significant zero-field splitting (ZFS) that results from spin-orbit mixing of excited states into the triplet ground state. The electronic consequences that might arise from the mixing of states as well as from a possible non-innocent behavior of the ligand have been explored by an experimental charge density study of [(btmgb)NiCl2] at low temperatures (7 K). Here, the presence of ZFS was identified as one potential reason for the flat ∢Cl-Ni-Cl deformation potential and the distinct differences between the ∢X-Ni-X valence angles observed by experiment and predicted by DFT. An analysis of the topology of the experimentally and theoretically derived electron-density distributions of [(btmgb)NiCl2] confirmed the strong donor character of the bisguanidine ligand but clearly ruled out any significant non-innocent ligand (NIL) behavior. Hence, [(btmgb)NiCl2] provides an experimental reference system to study the mixing of certain excited states into the ground state unbiased from any competing NIL behavior.